X-Linked Retinoschisis and a Coats-Like Response in the Setting of Retinopathy of Prematurity. (November 2020) - Fan, Kenneth C.; McAllister, Mark A.; Yannuzzi, Nicolas A.; Patel, Nimesh A.; Prakhunhungsit, Supalert; Negron, Catherin I.; Capó, Hilda; Berrocal, Audina M.
Purpose: This case report describes a unique case of a young patient with retinopathy of prematurity (ROP), a unilateral Coats-like response, and X-linked retinoschisis (XLRS). Methods: A 9-year-old boy with a history of regressed ROP presented with a unilateral Coats-like response, subretinal exudation, and XLRS. Examination and imaging findings demonstrated a highly unique combination of bilateral retinoschisis and a dramatic unilateral Coats-like response with a large schisis cavity. Results: Treatment with laser photocoagulation and anti-VEGF therapy led to resolution of the subretinal exudative changes. Conclusions: This is the first published description to our knowledge of a patient with a Coats-like response, XLRS, and a history of regressed ROP with resolution after treatment.